Freshwater Prawns: Biology and Farming - New, Michael Bernard; Valenti, Wagner Cotroni [UNESP]; Tidwell, James H.; D'Abramo, Louis R.; Kutty, Methil Narayanan (Wiley, 2009)
Covering general biology and every aspect of farming freshwater prawns, from current research to development and commercial practice, this has become widely viewed as a landmark publication in the field. The well-known team of editors, New, Valenti, Tidwell, D'Abramo and Kutty, have gathered cutting-edge contributions from the world's leading experts to provide farm personnel, business managers, researchers and invertebrate, freshwater and crustacean biologists with an essential resource. © 2010 Blackwell Publishing Ltd.